Es ist
\( f(x) = \frac{1}{2}\cdot \left(e^{x} + e^{-x} \right) \),
somit
\( f'(x) = \frac{1}{2}\cdot \left(e^{x} + (-1)\cdot e^{-x} \right) \),
oder
\( f'(x) = \frac{1}{2}\cdot \left(e^{x} - e^{-x} \right) \)
Zusammengefasst ergibt sich auf diese Weise für die ersten vier Ableitungen
\( \quad f(x) = \frac{1}{2}\cdot \left(e^{x} + e^{-x} \right) \)
\( \quad f'(x) = \frac{1}{2}\cdot \left(e^{x} - e^{-x} \right) \)
\( \quad f''(x) = \frac{1}{2}\cdot \left(e^{x} + e^{-x} \right) = f(x) \)
\( \quad f'''(x) = \frac{1}{2}\cdot \left(e^{x} - e^{-x} \right) = f'(x) \)
\( \quad f''''(x) = \frac{1}{2}\cdot \left(e^{x} + e^{-x} \right) = f(x) \)